2022
DOI: 10.1037/fsh0000667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on home visiting services for vulnerable families: A cross-state analysis of enrollment, engagement, and attrition patterns.

Abstract: Introduction: COVID-19 has resulted in massive health and economic consequences, with effects felt most acutely by populations that were disadvantaged prior to the pandemic. For families with young children, the effects have been compounded by service interruptions, though there is a lack of empirical evidence that demonstrates how COVID-19 has affected home visiting programs. This cross-state study is the first to examine the effects of the pandemic on home visiting enrollment, engagement, and retention patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Many parents of this medically complex patient cohort reported removing their children from in-person school environments or not allowing in-home care providers (i.e., care managers, therapists, nurses) into the home during that period in order to limit potential exposures. This is reflected in published data that showed a decrease of enrollment in home visiting services by 33–36% during the COVID pandemic ( 14 ). For CMC, the likelihood of COVID-19 exposure early in the pandemic reflected trends in the general population, most notably higher exposure risk in non-White racial groups, though not statistically significant in our analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Many parents of this medically complex patient cohort reported removing their children from in-person school environments or not allowing in-home care providers (i.e., care managers, therapists, nurses) into the home during that period in order to limit potential exposures. This is reflected in published data that showed a decrease of enrollment in home visiting services by 33–36% during the COVID pandemic ( 14 ). For CMC, the likelihood of COVID-19 exposure early in the pandemic reflected trends in the general population, most notably higher exposure risk in non-White racial groups, though not statistically significant in our analysis.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, home visiting programs rapidly adapted their models and service delivery in the onset of the COVID-19 pandemic (Williams et al 2021 ). Multiple studies of home visiting programs around the United States have demonstrated how HVs were able to continue to serve families throughout the COVID-19 pandemic (Rybińska et al 2022 ; Marshall et al 2020 ; Traube et al 2022 ; Roben et al 2022 ), with a couple studies finding a slight decline in program participation (Rybińska et al 2022 ; Mersky et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%